Investigation on Brazilian physiotherapists experiences and practice on palliative extubation - Agostini, Ana Paula Ragonete dos Anjos; Ferreira Arcuri, Juliano; Della Via, Fabiana; Lima, Lorrayne Camila; Aquino, Luana Carolina; Kosour, Carolina (Fisioterapia & Saúde Funcional, 2025)
Introduction: Mechanical-ventilation withdraw and endotracheal tube removal controversies are responsible for some difficulties surrounding these procedures in patients receiving palliative care. The aim of this study is to identify experiences, perceptions and practices of Brazilian physiotherapists regarding palliative extubation. Method: Prospective mixed methods study, with two moments, an online survey followed by semi-structured interviews. Professional profile, and practice prior, during and after palliative extubation. The variables were distributed in frequencies and described in percentages. Results: 54 physiotherapists answered the interviews, and 17 were excluded. The associated factors with palliative extubations were prognosis (94%), quality-of-life after intensive care unit (86%). The physiotherapy procedures used prior to extubation were endotracheal suctioning (95%), oral suctioning (97%), cuff deflation (100%). Most used mechanical-ventilation parameters were FiO2 21%, PEEP 5cmH2O and PS 7cmH2O (51%). The decisions after extubation were not administrate oxygen or other respiratory support (35%) and using 1-4L/min oxygen (22%). The most common complication was dyspnea (64%). Conclusion: Brazilian physiotherapists participate in palliative extubation. Symptom control and respiratory comfort were the priority When deciding for do not administrate oxygen or other ventilatory support after extubation.